Modernization of family farms improves the sustainability of food security for farm households in Burkina Faso - Bougma, Moussa; Kaboré, Sidbewendé Théodore; Becquey, Elodie (Academic Journals, 2021)
Family farms are poorly modernized in Burkina Faso despite their predominance in the country’s agriculture and their major contribution to national food production. Convincing evidence of the contribution of family farm modernization to food security is needed to support advocacy. This study used data from recent national longitudinal surveys and Cox semi-parametric regression methods to explore the effect of factors of modernization on the food security of farm households in Burkina Faso. The results showed that the training of agricultural workers, ownership of traction animals, and use of improved seeds reduced the risk of food-secure households falling into food insecurity by 22.8, 21.6, and 14.9%, respectively. These three factors significantly determine the stability of households’ food security, suggesting that the modernization of family farms could contribute to the prevention of food insecurity in Burkina Faso. A key strength of this study is that it was able to capitalize on the wealth of these data, which come from national surveys that are representative of farm households at the provincial level, longitudinal and prospective, making it possible to track the same households over time, at an annual frequency.